SPECIFICS AND FUNCTIONS OF PERSONAL BIBLIOGRAPHIC INFORMATION - RAUDYTĖ, NIJOLĖ (Knygotyra, 2012)
On the grounds of the writings and publications of Lithuanian and foreign bibliography research workers as well as the empirical material of the author’s study, the article deals with the situation of personal bibliographic information resources in Lithuania, their functional possibilities and the specifics of their practical use. Referring to the fact that the essence of personal bibliographic information is the reflection of a personality’s intellectual and creative potential, attention is drawn to the functions performed in the sociocultural system and to their connection with the methodology of compiling these resources. The increasing volume of publishing Lithuanian printed personal bibliographic information resources demonstrates their popularity. However, nowadays it becomes more and more obvious that the processes of their preparation are not effective, and also the methodology is a subject of dispute. In such a situation, it means that the possibilities of the practical use of personal bibliographic information resources become limited, and often the resources cannot fully serve their true purpose. Thus, we may come to the conclusion that at present a new systemic approach to personal bibliographic information, its specific functions and features as well as the corresponding methodological solutions are necessary. All the processes of preparing and functioning personal bibliographic information resources shall be aimed at reveling their functional possibilities.
Keywords: ...